Effect of Adjusting for Particle-Size Distribution of Cement on Strength Development of Concrete - Daegeon Kim (Advances in Materials Science and Engineering)
The massive construction projects such as nuclear power plants and gas storage plants operate their own batch plants for appropriate supply of a massive amount of ASTM Type I cement. The batch plants have difficulty responding to diversifying consumer requirements such as early strength development of concrete under the current limited production line of cement. In order to respond to the needs, this study collected several sizes of cement particles from different filters at a cement plant, and conducted the adjustment of cement particle-size distribution to enhance the properties of concrete based on ASTM Type I cement. This paper shows the chemical properties and physical tests such as setting time and compression tests considering the effects of the distribution of cement particles. Also, the classification based on cement particle-size distribution was defined as FMC (fineness modulus of cement). As FMC increased, compressive strength was relatively low at early age but the difference became smaller for later age. The test results show the effects of the adjusted mix proportion considering particle-size distribution of cement on strength development of concrete. Therefore, it is possible to see that customized cement or concrete can be manufactured in response to various consumer requirements by introducing such method that by-passes and collects fine or coarse cement in the cement-crushing process and then re-mixes them with OPC ASTM Type I cement depending on FMC.